Biological Activities of Secretory RNases: Focus on Their Oligomerization to Design Antitumor Drugs - Gotte, Giovanni; Menegazzi, Marta (Frontiers in Immunology, 2019)
Ribonucleases (RNases) are a large number of enzymes gathered into different bacterial or eukaryotic super-families. Bovine pancreatic RNase A, bovine seminal BS-RNase, human pancreatic RNase 1, angiogenin (RNase 5), amphibian onconase belong to the pancreatic type super-family, while binase and barnase deserve to be highlighted within bacterial RNases N1/T1 family. In physiological conditions, most RNases secreted in the extracellular space counteract the undesired effects of extracellular RNAs and become protective against infections. Instead, if they enter the cell, RNases can digest intracellular RNAs becoming cytotoxic and advantageous tasks against malignant cells. Their biological activities have been investigated either in vitro, toward a number of different cancer cell lines, or sometimes in vivo to test their potential therapeutic use. However, immunogenicity or other undesired effects have been sometimes associated to their action. Nevertheless, the use of RNases in therapy remains an appealing strategy for some still incurable tumors, such as mesothelioma, melanoma, or pancreatic cancer. The RNase inhibitor (RI) present inside almost all cells is the most efficacious sentry to counteract the ribonucleolytic action against intracellular RNAs because it forms a tight, irreversible and enzymatically inactive complex with many monomeric RNases. Therefore, dimerization or multimerization could represent a useful strategy for RNases to exert a remarkable cytotoxic activity by evading the interaction with RI by steric hindrance. Indeed, the majority of the mentioned RNases can hetero-dimerize with antibody derivatives, or even homo-dimerize or multimerize, spontaneously or artificially. This can occur through weak interactions or upon introducing covalent bonds. Immuno-RNases, in particular, are fusion-proteins representing promising drugs by combining high target specificity with easy delivery in tumors. The results concerning the biological features of many RNases reported in literature are described and discussed in this review. Furthermore, the activities displayed by some RNases forming oligomeric complexes, the mechanisms driving toward these supramolecular structures, and the biological rebounds connected are analyzed. These aspects are offered with the perspective to suggest possible efficacious therapeutic applications for RNases oligomeric derivatives that could contemporarily lack, or strongly reduce, immunogenicity and other undesired side-effects.